STIMULATING THE DEVELOPMENT OF RESIDENTIAL DEVELOPMENT THROUGH MORTGAGE LENDING - Maryna Bochkarova (Izdevnieciba "Baltija Publishing", 2024)
The article is devoted to stimulating the development of housing construction through mortgage lending. The purpose of the article is to determine the role of mortgage lending in the development of the housing sector, in particular through its impact on supply and demand in the real estate market and pricing in this sector. In the course of the research, data analysis, correlation analysis, and methods of forecasting economic trends were used. Graphical methods were also used to provide a clear understanding of how changes in the mortgage market affect the development of the real estate sector. The results of the study show that mortgage lending is a key element in stimulating the development of the housing sector, as it not only directly facilitates access to finance for potential property buyers, but also indirectly affects the pricing and investment attractiveness of the housing sector. The paper shows that fluctuations in mortgage rates have a significant impact on the dynamics of supply and demand in the residential real estate market, as well as on price trends. In particular, rising mortgage rates tend to reduce demand for housing, as households expect better investment opportunities. There is also a strong correlation between mortgage rate increases and slower price growth. The expansion of the mortgage lending market and, consequently, a reduction in mortgage rates boosts supply in the real estate market. Nevertheless, it is found that such changes can have complex and ambiguous consequences, including the risks of market overheating and the formation of price "bubbles" that threaten the stability of the sector in the long run. In addition, the study found that mortgage lending facilitates the implementation of new construction projects and the expansion of the housing stock, which is an important factor in stimulating economic growth. At the same time, the analysis showed that the impact of mortgage rates on the real estate market depends on a wide range of factors, including the economic situation, central bank policy, consumer confidence and other macroeconomic indicators. The practical significance of the publication is to provide recommendations for the development of a balanced policy in the field of mortgage lending aimed at supporting the stable development of the housing sector and preventing potential destabilising factors in the real estate market.